A close scrutiny of dApps and developing an e-voting dApp using Ethereum Blockchain. (18th August 2021) - Banupriya, N.; Pooja, G.; Nevetha, S.; Roopini, J.; Nivedhitha, M.
In the expeditiously advancing technological world, with the advent of IoT and big data, every day new people and devices which store highly sensitive personal data are getting connected. For instance, your Google home is listening to you and collecting data, your Facebook knows a lot about you; Amazon's Alexa gets to know our everyday wants. This implies that our data is used to spy on us for advertising purposes, hence these siren servers make the overall profit off us. This paper throws light on developing a dApp (decentralised application) that could be used in a voting system. Everything around us is digitising which does not mean we are moving towards a safe and secured scheme, thus the revolutionary Blockchain technology is used to deploy an e-voting system (Giorgino, 2018) and this is done using the Ethereum Blockchain (Wang et al., 2018).